PRAKTIK MEKANISME PENETAPAN HARGA JUAL BELI PADI DI KABUPATEN ACEH BESAR - Darmawan, Reza; Armiadi Musa; Hafas Furqani (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2022)
The purpose of this study is to discuss the practice of determining the selling and buying price of rice that is practiced by the people in Aceh Besar district. In this practice, there are two times for determinations the sale and purchase price of rice which is considered to contain an element of gharar in the second price determination. This research will explain: how the mechanism of the practice, a review of Islamic law related to the practice, whether the practice can be practiced in other areas. This study uses field research methods with data collection techniques in the form of interviews. The results of the study concluded: (1) In the practice of two times price determination buying and selling rice, there are three types of contracts used, that is the ba'i, hybrid contract between ba'i and wadiah and a hybrid contract between ba'i and qardh. (2) The practice using a ba'i is legal by refers to the rules of ushul fiqh related to the basic law of muamalah that is mubah. The legality is also supported by urf which is able to bring benefit even though it contains elements of gharar in it. The element of gharar in the second price fixing is considered gharar yasir which is legal because it has become 'urf that is able to present benefits and mutual pleasure towards the consequences that arise from the gharar element. Two other types of contracts, a hybrid contract between ba’i with wadiah and a hybrid contract between ba’i with qardh according to the Islamic law riview, they are not contrary to Islamic Law. (3) Although in real terms this practice can increase farmers' income, this practice cannot be practiced in other areas. Keywords: Price determination mechanism, Gharar, Hybrid Contract